Professional ethics and the labyrinth of precarisation: challenges and resistance in the work of Social Workers - Fagundes, Anderson da Silva; Reidel, Tatiano (Argumentum, 2025)
This article analyses the professional ethics of social workers in the context of labour precarisation based on bibliographic and empirical research conducted with 168 professionals in the state of Rio Grande do Sul, Brazil. The findings reveal a resurgence of conservatism in everyday professional practice, shaped by processes of alienation, sickness, and intensified exploitation. Against this background, the study identifies ethical-political strategies as both individual and collective forms of resistance. It highlights the paradox between the formal adherence to the ethical-political project and the persistence of conservative personal values. The study concludes by emphasising the need to overcome alienation and to strengthen professional ethics as a critical mediation between objective conditions and professional action, reaffirming its historical, collective, and emancipatory character.